2005
DOI: 10.1002/jgm.748
|View full text |Cite
|
Sign up to set email alerts
|

Highly branched HK peptides are effective carriers of siRNA

Abstract: Both the degree of complexity and the sequence specificity are important factors to be considered for developing the HK carrier of siRNA. In particular, we found that certain branched HK polymers (H3K8b, H3K8b(+RGD), and similar structural analogs) with eight terminal branches and a histidine-rich domain were effective carriers of siRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 17 publications
3
138
0
Order By: Relevance
“…Rapid degradation of arginyl peptides by intracellular trypsin-like proteases could additionally account for the low cytotoxicity of the tested polypeptide (Futaki et al 2001b). Branched histidine and lysine polymers have been used in a similar manner for siRNA transfection approaches, demonstrating that the ability to successfully transfect DNA does not per se qualify for effective siRNA transfection (Leng et al 2005). Other approaches used siRNA chemically coupled to the membrane permeant peptides penetratin1 or transportan via a disulfide bond and have equally shown to mediate efficient transfection of primary neurons (Davidson et al 2004;Muratovska and Eccles 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid degradation of arginyl peptides by intracellular trypsin-like proteases could additionally account for the low cytotoxicity of the tested polypeptide (Futaki et al 2001b). Branched histidine and lysine polymers have been used in a similar manner for siRNA transfection approaches, demonstrating that the ability to successfully transfect DNA does not per se qualify for effective siRNA transfection (Leng et al 2005). Other approaches used siRNA chemically coupled to the membrane permeant peptides penetratin1 or transportan via a disulfide bond and have equally shown to mediate efficient transfection of primary neurons (Davidson et al 2004;Muratovska and Eccles 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the modification of a polylysine dendritic scaffold with HIV tat protein sequences, which are described to be able to facilitate cellular and nuclear transport [148]; the modified polylysine dendrimers containing lipidated units developed by Bayele et al [149], which were able to efficiently deliver oligonucleotides into the nucleus; and the cell penetrating peptide bearing polylysine dendrimers developed by Toth and Minchin's group [150,151]. On the other hand, Mixson et al studied the effect of the histidine loading of different His/Lys-based dendrimers [152][153][154]. This was a development of his significantly enhanced DNA delivery in a variety of cell lines.…”
Section: Dendrimersmentioning
confidence: 99%
“…Leng et al designed branched histidine-lysine (HK) peptides for the delivery of siRNAs and showed that H 3 K8b/siRNA polyplex inhibited beta-galactosidase expression by more than 80% in an endothelial cell line (SVR-bag4) (Leng et al, 2005). The work demonstrated that the histidine-rich domain and the terminal arms of H 3 K8 were crucial for siRNA delivery.…”
Section: Polypeptidesmentioning
confidence: 99%